United Republic of Tanzania : Second Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Tanzania's Second Review Under the Policy Support Instrument (PSI). Tanzania's macroeconomic performance remains strong. Program performance since the last review has been uneven. All end-2014 assessment criteria were met, though the indicative target on tax revenue collection was missed. Good progress was made on structural benchmarks. Shortfalls in domestic revenue continued in early 2015, and delays were incurred in mobilizing external financing and adjusting expenditure in the context of the mid-year budget review. The IMF staff recommends completion of the second PSI review and modification of assessment criteria on net international reserves and net domestic financing for end-June 2015.